РОЛЬ І ЗНАЧЕННЯ ДЕРЖАВНОГО БОРГУ В ГРОШОВО-КРЕДИТНІЙ ТА ПОДАТКОВІЙ ПОЛІТИЦІ УКРАЇНИ - Лисяк, Любов Валентинівна (Науковий журнал «Світ фінансів», 2017)
Лисяк Л. В. Роль і значення державного боргу в грошово-кредитній та податковій політиці України. Охарактеризовано роль і значення державного боргу в грошово-кредитній та податковій політиці України. Проаналізовано структуру та динаміку державного боргу. Здійснено порівняльний аналіз динаміки державного та гарантованого державою боргу України з динамікою облікової процентної ставки Національного банку України (індикатора грошово-кредитної політики держави) та рівнем загального податкового навантаження відповідно до міжнародного рейтингу легкості ведення бізнесу. Досліджено загальні тенденції взаємного впливу аналізованих показників та надано рекомендації щодо удосконалення управління державним боргом в Україні за сучасних умов. Лысяк Л. В. Роль и значение государственного долга в денежно-кредитной и налоговой политике Украины. Дана характеристика значения государственного долга в денежно-кредитной и налоговой политике Украины. Проанализированы структура и динамика государственного долга. Осуществлен сравнительный анализ динамики государственного и гарантированного государством долга Украины с динамикой учетной процентной ставки Национального банка Украины (индикатора денежно-кредитной политики государства) и уровнем общей налоговой нагрузки в соответствии с международным рейтингом легкости ведения бизнеса. Отмечены общие тенденции взаимного влияния рассматриваемых показателей и даны рекомендации по совершенствованию управления государственным долгом в Украине в современных условиях. Lysjak L. The role and value of public debt in monetary and fiscal policy of the Ukraine. Introduction. In conditions of the crisis development of the national economy in order to ensure financial stability, the question of the meaning and role of public debt in monetary and fiscal policy of the state is especially important. Lack of coordination of monetary and fiscal policy affects on the state of public finances. As a result of this mismatch is high yield bonds of government debt, which stimulates an increase in the cost of funds in the money market and thereby undermine the efforts of the central bank to lower interest rates.Purpose. Prove that based on theoretical and analytical studies of the role and value of public debt in monetary and fiscal policy of the state (for example, Ukraine).Results. Comparative analysis of the dynamics of public and publicly guaranteed debt of Ukraine, with dynamics of the discount interest rate of the National Bank of Ukraine (the indicator of monetary policy) and the level of the overall tax burden under international ranking of ease of doing business, showed that changes in the level of public debt of foreign currency (USA dollars) has no significant effect on the interest rate, but given the significant devaluation of the currency and the need to curb inflation, rising debt burden was one of the basic reasons for the increase of NBU discount rate in 2014–2015 years. This fact testifies to the growth of public debt, due to changes in foreign currency and the impact on the interest rates of money market of Ukraine as part of monetary policy. At the same time, minimizing debt servicing costs as a task of monetary policy depends on interest rates (in the short run, monetary policy can reduce the debt payments, keeping interest rates at the low level). In the long term deployment of inflation as a result of growth in the money supply with the aim of keeping short-term interest rates at a low level indicating that the unreasonableness of such policy.Conclusion. State policy of Ukraine in the tax and monetary sphere, should take into account the interdependence of the debt policy, and together provide a balance of financial benefits to the economy by attracting debt funds and the cost of repayment and debt service (providing a combination of tax and debt policy to stimulate business activity); minimizing the risks of the investor (which ultimately will reduce interest rates on loans and interest rates of money market countries); the combination of the size of the debt limit with the standards that ensure operation of automatic stabilizers and allow for flexibility in the application of counter-cyclical fiscal policy to counter the significant downturn in the economy; reducing the cost of borrowing for the needs of the state (through the optimal combination of monetary and debt policy).